A molecular dynamics study of the sputtering processes of beryllium species by hydrogenic plasma - Alexander Liptak; Kerry D. Lawson; Mohammad I. Hasan (Scientific Reports)
Abstract The plasma-facing components of nuclear fusion reactors are continuously subjected to high thermal loads and bombardment by hydrogenic ions, resulting in erosion of the first-wall material and sputtering of atomic and molecular species into the edge plasma. The management of reactor component lifetimes and control of sputtered plasma impurities remain open problems in fusion research, where quantifying the sputtering yields and understanding the sputtering processes of each impurity species is pivotal for planning an effective maintenance schedule and ensuring optimal plasma performance. Although the sputtering of atomic species is historically well-established, the sputtering of molecules from metallic first-wall materials such as beryllium has only recently been confirmed possible and relevant for fusion reactors. In this study, a molecular dynamics model is used to investigate the sputtering of atomic beryllium, Be $$_2$$ 2 dimers, Be $$_3$$ 3 trimers, beryllium hydrides, and hydrogenic dimers. The sputtering yield of each species is reported, and the observed ion trajectory preferential sputtering behaviour is presented; beryllium lattice thermal effects as well as bombarding ion isotope effects are discussed where relevant. A theoretical description of the universal sputtering yield relation and its various corrections are explored in detail, and the molecular dynamics model is benchmarked against analytical, computational and experimental data.